Neoplasms of the canine and feline central nervous system: 20-year study (Research, Society and Development, 2021)
The aim of this study was to evaluate the epidemiological and pathological aspects of neurological neoplasms in canines and felines referred to the Laboratório Regional de Diagnóstico of the Faculdade de Veterinária of the Universidade Federal de Pelotas (LRD/FV/UFPel) over a period of 20 years. The protocols for necropsy of canines and felines sent to the LRD/FV/UFPel from January 2000 to December 2020 were reviewed, and cases with a diagnosis of primary and secondary neurological neoplasia were selected. From these, information regarding age, sex, race, clinical signs, macroscopic and histopathological findings were analyzed. During the study period, 35 cases of neoplasms in the central nervous system of canines and six in felines were diagnosed. In both species, neoplasms were more frequent in females, mixed breed animals over five years of age, with secondary tumors being the most prevalent. The most affected neuroanatomical region in canines was the thalamus-cortical region and in felines the spinal cord. In dogs, the most frequent neurological clinical sign was seizure and in cats there was no higher occurrence of any clinical sign. The absence of neurological signs was observed in 37.5% of canines and 50% of felines. The main neoplasms related to the cause of death of dogs and cats in this study were the secondary ones, with metastasis from mammary carcinoma being the main diagnosis, and in many cases neurological clinical signs may not be observed.